2022
DOI: 10.5336/nurses.2022-91112
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Anxiety Levels of Patients Before Laparoscopic Cholecystectomy Surgery on Postoperative Pain and Sleep: Descriptive Research

Abstract: Laparoskopik kolesistektomi, safra kesesinin laparoskopik girişimlerle kesilerek çıkartılması işlemidir ve daha az cerrahi travmaya sebep olması, ameliyat son-rası sürecin daha iyi olması, hızlı iyileşmeyi desteklemesi sebebiyle semptomatik safra taşlarının tedavisinde sık kullanılan bir yöntem olarak tercih edilmektedir. [1][2][3]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…[ 11 ] Surgery can lead to anxiety in individuals owing to hospitalization, separation from their families, disruption of their daily routines, unfamiliar medical procedures, negative experiences encountered during the perioperative process, and postoperative pain. [ 42 ] It has been reported that the age of patients scheduled for surgical interventions often corresponds to increased anxiety and decreased satisfaction levels. [ 23 , 42 ] Patient satisfaction is a pivotal metric in assessing the quality of perioperative nursing care, and perceived quality of care is posited to influence patient levels of anxiety and contentment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 11 ] Surgery can lead to anxiety in individuals owing to hospitalization, separation from their families, disruption of their daily routines, unfamiliar medical procedures, negative experiences encountered during the perioperative process, and postoperative pain. [ 42 ] It has been reported that the age of patients scheduled for surgical interventions often corresponds to increased anxiety and decreased satisfaction levels. [ 23 , 42 ] Patient satisfaction is a pivotal metric in assessing the quality of perioperative nursing care, and perceived quality of care is posited to influence patient levels of anxiety and contentment.…”
Section: Discussionmentioning
confidence: 99%
“…[ 42 ] It has been reported that the age of patients scheduled for surgical interventions often corresponds to increased anxiety and decreased satisfaction levels. [ 23 , 42 ] Patient satisfaction is a pivotal metric in assessing the quality of perioperative nursing care, and perceived quality of care is posited to influence patient levels of anxiety and contentment. Particularly in the perioperative process, patients should receive comprehensive psychological support to alleviate their anxiety levels.…”
Section: Discussionmentioning
confidence: 99%